2020
DOI: 10.1093/condor/duz071
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success of the threatened San Clemente Bell’s Sparrow (Artemisiospiza belli clementeae) in recovering habitats is similar to success in historical habitat

Abstract: The San Clemente Bell’s Sparrow (Artemisiospiza belli clementeae) is a federally threatened subspecies endemic to San Clemente Island, California. Previous research suggested dependence on boxthorn (Lycium californicum) as breeding habitat and nesting substrate; however, this conclusion was based on data collected when introduced feral ungulates had severely degraded the soil and vegetation cover. Since removal of the ungulates, native vegetation has gradually increased and the San Clemente Bell’s Sparrows hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Although previous research found SCI Bell's Sparrows nested almost exclusively in California boxthorn (Lycium californicum)-dominated habitat (Kaiser et al 2009, Hudgens et al 2011, during this study period the sparrows also occupied the recently recovered alternative shrub cover, including sagebrush (Artemisia californica and A. nesiotica). We expected higher nest success in sagebrush than other substrates, given Bell's Sparrows affinity for sagebrush in other systems (Rich 1980, Misenhelter andRotenberry 2000), and observed higher nest success in taller shrubs (Meiman et al 2020). We expected that early-season nests would have higher survival than lateseason nests, given that research in semi-desert species suggests resources may decline late in the breeding season (Ruth and Skagen 2018).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although previous research found SCI Bell's Sparrows nested almost exclusively in California boxthorn (Lycium californicum)-dominated habitat (Kaiser et al 2009, Hudgens et al 2011, during this study period the sparrows also occupied the recently recovered alternative shrub cover, including sagebrush (Artemisia californica and A. nesiotica). We expected higher nest success in sagebrush than other substrates, given Bell's Sparrows affinity for sagebrush in other systems (Rich 1980, Misenhelter andRotenberry 2000), and observed higher nest success in taller shrubs (Meiman et al 2020). We expected that early-season nests would have higher survival than lateseason nests, given that research in semi-desert species suggests resources may decline late in the breeding season (Ruth and Skagen 2018).…”
Section: Introductionmentioning
confidence: 89%
“…The maritime desert scrub habitat at low elevation on the western side consisted of California boxthorn, interspersed with forbs and cactuses, including prickly-pear (Opuntia littoralis and Opuntia oricola), coastal cholla (Cylindropuntia prolifera), and golden-spined cereus (Bergerocactus emoryi; S. T. Meiman, S. A. Munoz, E. E. Deleon, B. Sandstrom, S. Nefas, and A. S. Bridges, 2017, unpublished manuscript). Bell's Sparrows have historically nested in this boxthorn-associated community at high densities (Meiman et al 2020). Along the higher elevation western terraces and eastern slopes, various combinations of cactus and forbs occurred, with small patches of low shrubs, the most common of which were sagebrush, coyote brush (Baccharis pilularis), and island morning glory (Calystegia macrostegia amplissima; Meiman et al 2017, unpublished manuscript).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations